Evaluation of Effect of Calcium on Scale Formation and Corrosivity of Groundwater Using GIS - Ravi Kumar, K.; Das, A.; Mukesh, G.; Ramasamy, Nagarajan (Technoscience Publications, 2014)
The ancient Thanjavur population located in delta of River Cauvery had been dependent on surface water for drinking until recently, wherein there is an incremental rise in augmented bore-well water supply. Incidentally, there have been observations of moderate to high scale formations by the groundwater during domestic heating, as well as consistently high record of kidney-stone (mostly calcium oxalates) occurrence in the city and its suburbs. The present work focuses on calcium content, its desirability level and the corrosion/scaling coefficients. One hundred two (102) samples were collected prior to monsoon season in the year 2008 from the study area for study of various physico-chemical parameters. In order to estimate scalability and corrosivity, two standard indices (namely Langelier Saturation Index and Ryznar Saturation Index) were used. GIS has been used to develop integrated maps for demarcating zones of different calcium concentrations in groundwater and its relation with scale and corrosion formation tendencies.